2011
DOI: 10.5194/angeo-29-1605-2011
|View full text |Cite
|
Sign up to set email alerts
|

Role of fine mode aerosols in modulating cloud properties over industrial locations in north India

Abstract: Abstract. The influence of aerosols on cloud properties over North India which includes the Indo-Gangetic Plain has been investigated for the years 2000 to 2010. During the years 2004, 2009 and 2010 there has been an abrupt increase in fine mode aerosol optical depth (AOD) inducing a sharp decline in cloud effective radius (CER) in the month of January. The following monsoon during these years was a failure in the region considered for the study. In the year 2010, a highest AOD value of 0.35 was recorded in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The aerosol indirect effect on the monsoon water cycle is still in an early stage of research. Evidence of reduction in cloud effective radius as a function of increasing AOD in northern India, consistent with the albedo effect [ Twomey , ], has been found from MODIS and Aerosol Robotic Network (AERONET) data [ Abish and Mohanakumar , ; Tripathi et al, ; Panicker et al, ; Cherian et al, ]. Analysis of the microphysical structure of deep convective clouds over the Indian Peninsular region observed during the Cloud Aerosol Interaction and Precipitation Enhancement Experiment (CAIPEEX) showed that polluted clouds had larger concentrations of smaller drops.…”
Section: The Role Of Aerosols In Acpcmentioning
confidence: 75%
“…The aerosol indirect effect on the monsoon water cycle is still in an early stage of research. Evidence of reduction in cloud effective radius as a function of increasing AOD in northern India, consistent with the albedo effect [ Twomey , ], has been found from MODIS and Aerosol Robotic Network (AERONET) data [ Abish and Mohanakumar , ; Tripathi et al, ; Panicker et al, ; Cherian et al, ]. Analysis of the microphysical structure of deep convective clouds over the Indian Peninsular region observed during the Cloud Aerosol Interaction and Precipitation Enhancement Experiment (CAIPEEX) showed that polluted clouds had larger concentrations of smaller drops.…”
Section: The Role Of Aerosols In Acpcmentioning
confidence: 75%
“…The proliferation of the absorbing aerosols during the pre-monsoon season is shown to have modulated the cloud properties and on the overall performance of the Indian summer monsoon (Menon et al, 2002;Lau et al, 2006;Meehl et al, 2008;Gautam et al, 2009;Abish and Mohanakumar, 2011). Such an alteration in the normal weather pattern demands attention in a meteorologically sensitive region because of the location of Monsoon Trough and the apparent position of inter tropical convergence zone (ITCZ) during the summer monsoon season (June to September).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggested that aerosolinduced changes in cloud dynamics and microphysics are the potential causal mechanism for the aerosol-cloud-rainfall linear dependence. Over the Indian region, previous studies have compared MODIS-observed cloud microphysical properties between low-and high-aerosol loading to demonstrate the aerosol microphysical effect and its linkage to interannual variations in seasonal rainfall (Abish and Mohanakumar, 2011;Panicker et al, 2010;Ramachandran and Kedia, 2013). Aerosol impacts on cloud microphysics over central India based on ground-based measurements are also evident (Harikishan et al, 2016;Tripathi et al, 2007).…”
Section: The Effect Of Underrepresentation Of the Wet-scavenging Effementioning
confidence: 99%